Experimental survey of the Ground Penetrating Radar (GPR) in the study of the Aturiaí river (Bragança Coastal Plain, northeast of Pará) (Research, Society and Development, 2020)
This article shows the Ground Penetrating Radar (GPR) experiment applied to the Aturiaí river (Augusto Corrêa, Pará, Brazil), which is one of the most important in the hydrographic basin of the municipality of Augusto Corrêa. This river has a length of 15 km and a width varying between 8 m and more than 200 m at the mouth, with depth between 0,8-1 m at the headwater, and 1,2-1,5 m at the middle and 1,6-2 m at the mouth. During the dry period, salinity is higher and registers values ​​between 0,05 (internal part) and 30,9 (mouth), very close to ocean salinity. The river runs through the mangrove on the Bragantine coastal plain. The results show that with the 200 MHz frequency antenna, the GPR is able to obtain records (radargrams) of the river's subsurface, over 3 m deep, reaching the baseline transgressive sequence (S1), consisting of sands and muds of marine/estuarine origin at the base (3-6 m). The granulometry of the sediments reveals that sand is the main dominant class (58%) at the bottom of the river, and the size of the particles decreases from upstream to mouth. The performance of the GPR in the detection of the strata of the Aturiaí river subfund was evaluated during a seasonal cycle, with high and low salinity.